2012
DOI: 10.3390/ijms13044367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Adenocarcinoma-Associated Gene AGR2 and the Intestinal Stem Cell Marker LGR5 as Biomarkers in Colorectal Cancer

Abstract: We aim to estimate the diagnostic performances of anterior gradient homolog-2 (AGR2) and Leucine-rich repeat-containing-G-protein-coupled receptor 5 (LGR5) in peripheral blood (PB) as mRNA biomarkers in colorectal cancer (CRC) and to explore their prognostic significance. Real-time PCR was used to analyze AGR2 and LGR5 in 54 stages I-IV CRC patients and 19 controls. Both mRNAs were significantly increased in PB from CRC patients compared to controls. The area under the receiver-operating characteristic curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 44 publications
1
43
0
1
Order By: Relevance
“…Our finding confirmed the previous studies indicating higher expression level of Lgr5 in PB of CRC patients compared to control group [57]. We also confirmed that Lgr5 expression was significantly higher in higher stages of CRC.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Our finding confirmed the previous studies indicating higher expression level of Lgr5 in PB of CRC patients compared to control group [57]. We also confirmed that Lgr5 expression was significantly higher in higher stages of CRC.…”
Section: Discussionsupporting
confidence: 95%
“…The correlation between Lgr5 expression level and clinicopathological features as well as clinical outcome of CRC patients has been discussed in depth throughout the literature [37][38][39]. In addition, the diagnostic and prognostic significance of circulating Lgr5 as a potential marker of CRC in PB has been recently reported [57]. Moreover, accumulating evidences have emphasized on the role of DCLK1 as a candidate of CSC markers in CRC patients [44,45].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[21][22][23][24][25]31 In this study, the effect of rhES-AuNPs on mCRC tumor growth in vivo was firstly evaluated. The results suggested that rhES-AuNPs experimental group could modulate vascular morphology in mCRC tumor and improve tumor hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that it is the stem cells within the circulating tumor cell pool that are responsible for metastatic disease progression: these cells are termed circulating tumor stem cells (CTSC) (33) (Figure 1). This view is bolstered by the presence of stem cell phenotypes CD26+ and CD133+ in CTCs of metastatic CRC patients (44,45) and the finding that increased expression of the exclusive stem cell marker leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5) in colorectal tumors indicates a poor prognosis (46,47).…”
Section: The Emerging Circulating Tumor Stem Cell Hypothesismentioning
confidence: 99%